2012
DOI: 10.1002/etc.1827
|View full text |Cite
|
Sign up to set email alerts
|

Mixture toxicity of wood preservative products in the fish embryo toxicity test

Abstract: Wood preservative products are used globally to protect wood from fungal decay and insects. We investigated the aquatic toxicity of five commercial wood preservative products, the biocidal active substances and some formulation additives contained therein, as well as six generic binary mixtures of the active substances in the fish embryo toxicity test (FET). Median lethal concentrations (LC50) of the single substances, the mixtures, and the products were estimated from concentration-response curves and correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The case of product A with the dissipated active substance IPBC demonstrates the importance of analytical verifications of nominal test concentrations in order to correctly define the composition of the mixture that is assessed. In a previous study with fish embryos , IPBC concentrations were found to drop to approximately 60% of the initial concentration after 48 h of exposure, while the concentrations of propiconazole and fenoxycarb remained stable. Yet, all mixture toxicity predictions and comparisons with observed toxicity ignored changes in the mixture composition during the exposure period.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The case of product A with the dissipated active substance IPBC demonstrates the importance of analytical verifications of nominal test concentrations in order to correctly define the composition of the mixture that is assessed. In a previous study with fish embryos , IPBC concentrations were found to drop to approximately 60% of the initial concentration after 48 h of exposure, while the concentrations of propiconazole and fenoxycarb remained stable. Yet, all mixture toxicity predictions and comparisons with observed toxicity ignored changes in the mixture composition during the exposure period.…”
Section: Discussionmentioning
confidence: 74%
“…It is important to note that algal growth inhibition was still the most sensitive measured endpoint for the toxicity of product B, thereby rendering the underestimation of Daphnia acute toxicity irrelevant in the context of an environmental risk assessment. Yet, this does not prove that mixture toxicity underestimation is in general only relevant for the endpoint that is the most sensitive for the individual mixture components (algae were more sensitive than Daphnia and fish embryos for all 3 active substances investigated). Let us assume that the degree of toxicity underestimation is very large for an endpoint that is not the most sensitive for any of the individual mixture components.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Such research has included in vitro and in vivo studies (Boyd et al, 2013; Cedergreen et al, 2012; Coors et al, 2012), toxicity assessment using combined effects models (Crépet et al, 2013; Hertzberg et al, 2013; Moser et al, 2012; Rider et al, 2008; Webster, 2013), evaluating stressor impacts environmentally (Allan et al, 2012; Florian et al., 2013; Løkke 2010), risk assessment studies (Johnson et al, 2013; Løkke et al, 2013; Meek, 2013; Moore and Teed, 2013) and examining chemical reactivity within complex mixtures (Goel et al, 2013). Although the specifics of such research vary, the common goal is improving the ability to predict the effects of exposure to chemical mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, if toxic compounds are not considered in a component based assessment, the calculated risk will be an underestimation of the actual risk of the biocidal product, see [25]. It is, however, impossible to provide a general estimate of the magnitude of such an underestimation, as this depends on the concentration and ecotoxicological potency of the compounds that are erroneously not included in the assessment.…”
Section: Non-consideration Of Relevant Ingredientsmentioning
confidence: 99%